Nerve Complications with Regional Anesthesia in Foot and Ankle Surgery Avoiding the Popliteal Fossa - Austin Gerwig MA, BS; Breanna Santoso; Maximilian George; Nicholas Cheney DO, FAOAO; Patrick O'Connor (Foot & Ankle Orthopaedics)
Category: Other Introduction/Purpose: Popliteal nerve blocks are often used to aid intraoperative general anesthesia and provide post-operative pain control for many foot and ankle surgeries. Unfortunately, there is conflicting data regarding complication rates from popliteal nerve blocks, specifically when comparing studies from (the) orthopedic and anesthesia literature. Orthopedic literature notes long term effects (foot drop/sensation deficits) whereas anesthesia literature focuses on immediate post-operative pain control. An approach to block more distal nerves and avoid the popliteal fossa altogether may provide equal anesthetic and pain relief with fewer motor and sensory complications. Our study seeks to address such complications by utilizing an alternative anesthetic approach that targets sensory distributions of nerves that may be affected during the procedure while avoiding major motor neve contributions within the popliteal fossa. Methods: We conducted a retrospective chart review between 2019 and 2023, analyzing complications associated with regional anesthesia achieved via a distal ankle block rather than a popliteal nerve block. Two hundred thirty-seven patients who underwent a variety of foot and ankle procedures (e.g., ankle arthroscopy, ankle fracture repair, cavovarus foot reconstruction, hallux valgus arthrodesis, lateral ankle stabilization, calf tendon revision, midfoot fusion, metatarsal arthrodesis) were included in this study. Results: Out of 237 patients who received a distal ankle block, only three patients were found to have superficial peroneal neuropathy confirmed with EMG, yielding a complication rate of 1.3%. Additionally, six patients required post-operative rescue block for pain control. The remaining 234 patients recovered without complications caused by the distal nerve block approach. Conclusion: The low rate of complications, specifically motor complications, from the distal nerve blocks demonstrate a beneficial alternative to the popliteal nerve blocks for various foot and ankle orthopedic surgeries. This finding is important to consider when choosing an appropriate approach to augment intraoperative general anesthesia accompanying foot and ankle surgeries in the outpatient setting.